2019
DOI: 10.1016/j.tcsw.2019.100030
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cell wall synthesis and metabolism during early germination of Blumeria graminis f. sp. hordei conidial cells induced in vitro

Abstract: As an obligate biotroph, Blumeria graminis f. sp. hordei ( Bgh ) cannot be grown in an axenic culture, and instead must be cultivated on its host species, Hordeum vulgare (barley). In this study an in vitro system utilizing n -hexacosanal, a constituent of the barley cuticle and known inducer of Bgh germination, was used to cultivate Bgh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…The accumulating data indicate that hardness, hydrophobicity, and waxy are the critical determinants of whether infection structures form normally (Dean, 1997;Shaw & Hoch, 2000). RT-qPCR results in the present study showed that AaCaM gene expression was differentially upregulated on both hydrophobic and pear wax surfaces (Figure 3), which largely indicates that hydrophobicity and pear wax are essential for inducing the infection structure differentiation, which was consistent with previous studies in B. graminis (Pham et al, 2019) and M. oryzae (Kijpornyongpan & Aime, 2020). The TFP treatment effectively inhibited appressorium formation in a concentration-dependent manner and was completely inhibitory at 30 μmol l −1 (Figure 4).…”
Section: Discussionsupporting
confidence: 92%
“…The accumulating data indicate that hardness, hydrophobicity, and waxy are the critical determinants of whether infection structures form normally (Dean, 1997;Shaw & Hoch, 2000). RT-qPCR results in the present study showed that AaCaM gene expression was differentially upregulated on both hydrophobic and pear wax surfaces (Figure 3), which largely indicates that hydrophobicity and pear wax are essential for inducing the infection structure differentiation, which was consistent with previous studies in B. graminis (Pham et al, 2019) and M. oryzae (Kijpornyongpan & Aime, 2020). The TFP treatment effectively inhibited appressorium formation in a concentration-dependent manner and was completely inhibitory at 30 μmol l −1 (Figure 4).…”
Section: Discussionsupporting
confidence: 92%
“…Proteomics approaches, based on mass spectrometry analysis, are useful for studying the protein profiles of plant pathogens. Until now most proteomics-based analysis of plant-biotrophic pathogen interactions has focused on resistance responses of the plant host (Lee et al, 2009;Lan et al, 2019) and few studies have investigated the pre-penetrative events that occur before these pathogens colonize host plant roots (Bheri et al, 2019;Pham et al, 2019). Detailed knowledge of the molecular events occurring during spore germination of S. subterranea could reveal new targets for control strategies focused on the pre-infection phase.…”
Section: Introductionmentioning
confidence: 99%
“…These genes play an important role in maintaining the life cycle of powdery mildew. For example, bgh00776 and bgh00774 (β-1,3-glucanosyltransferase) 17) play key roles in cell wall maintenance. Eight candidate secreted effector protein genes (bgh02536, 18) bghG000714000001001, bgh02072, bgh02386, bgh04794, bgh01776, bgh04522, and bghG004378000001001) have been studied and shown to have a function in virulence.…”
Section: Effects Of Flutianil On Gene Expression In the Basic Cell Function Of Bghmentioning
confidence: 99%
“…Eight candidate secreted effector protein genes (bgh02536, 18) bghG000714000001001, bgh02072, bgh02386, bgh04794, bgh01776, bgh04522, and bghG004378000001001) have been studied and shown to have a function in virulence. 17,19) The bgh04203 (CAP20-like protein) gene was reported as a strong candidate for pathogenicity factors in Bgh. 20) The flutianil treatment did not affect those constantly expressed genes of Bgh.…”
Section: Effects Of Flutianil On Gene Expression In the Basic Cell Function Of Bghmentioning
confidence: 99%